PENGARUH PROFITABILITAS DAN FREE CASH FLOW TERHADAP HARGA SAHAM - Aida Safana; Gabriela Nikita; Merisca Febriani (Indonesian Journal of Thousand Literacies, 2023)
Purpose to determine the effect of  profitability through measuring Return on Equity (ROE) and  Free cash flow on stock prices in consumer non-cyclicals sector companies. this research uses a quantitative method using secondary data taken from annual reports and financial reports on the Indonesia Stock Exchange (IDX). Using 9 sample companies in the Consumer non-cyclicals sector for the 2017-2021 period using the regression analysis test, the classic assumption test, the t test and the f test. By using SPSS 23 software. The results showed that profitability and free cash flow did not have a positive effect on stock prices, in other words the independent variables tested were rejected. this study only consisted of 45 samples. The author contributes from previous research by providing empirical evidence regarding the effect of profitability and free cash flow on stock prices in non-consumer cycle sectors. This research was conducted to support the same results from previous studies